Arch of the Setting Sun and the Arch of the Rising Sun - Bedford, Thomas A.:::::::::
Atop the Arch of the Setting Sun is the sculpture, "Nations of the West," and atop the Arch of the Rising Sun is the sculpture, "Nations of the East." View of the Fountain of the Setting Sun. All are located within the Court of the Universe.